Evaluasi Pembangunan dan Pengembangan Infrastruktur Hijau di Kabupaten Tangerang - Eko Adhy Setiawan; Hinijati Widjaja (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Green infrastructure development is an urgent need in metropolitan buffer zones such as Tangerang Regency, which face pressures from urbanization, industrialization, and environmental degradation. This study aims to evaluate the construction and development of green infrastructure in Tangerang Regency, focusing on its ecological, social, and governance functions. Using a qualitative approach with a case study design, the research was conducted over six months through in-depth interviews with stakeholders, field observations of green open spaces, city parks, and infiltration wells, and a review of policy documents and official reports. The results indicate that green infrastructure has had a positive impact on reducing microclimate temperatures, increasing social interaction, and partially reducing stormwater runoff. However, its distribution remains unequal, maintenance is minimal, community participation is unequal, and coordination between agencies tends to be fragmented. The study's conclusions emphasize that the success of green infrastructure cannot be measured solely by physical achievements; instead, sustainability, equitable access, and multi-stakeholder collaboration must be considered. This research's contribution lies in providing a multidimensional evaluation framework that can serve as a reference for local governments and stakeholders in designing more equitable, inclusive, and sustainable green infrastructure policies.